2006
DOI: 10.1128/aac.00490-06
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Membrane Disruption and Antibiotic Action against Pathogenic Bacteria by Designed Histidine-Rich Peptides at Acidic pH

Abstract: The histidine-rich amphipathic cationic peptide LAH4 has antibiotic and DNA delivery capabilities. Here, we explore the interaction of peptides from this family with model membranes as monitored by solid-state 2 H nuclear magnetic resonance and their antibiotic activities against a range of bacteria. At neutral pH, the membrane disruption is weak, but at acidic pH, the peptides strongly disturb the anionic lipid component of bacterial membranes and cause bacterial lysis. The peptides are effective antibiotics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
94
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 40 publications
7
94
0
Order By: Relevance
“…On the other hand, PMF dependent efflux pumps also appear able to import porcine, bovine and other AMPs, thereby promoting their activity [112][113][114] . The promotion of antimicrobial action by low pH has been reported for a number of AMPs, including human hepcidins 115 , gads 116 clavanins and styelins 117 from marine organisms, and a range of synthetic peptides [118][119][120][121] , along with the anticancer activity of a variety of AMPs 16 . For the most, part, these studies have focussed on cationic AMPs and there has been less research into the effects of pH on anionic AMPs 94,95 .…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, PMF dependent efflux pumps also appear able to import porcine, bovine and other AMPs, thereby promoting their activity [112][113][114] . The promotion of antimicrobial action by low pH has been reported for a number of AMPs, including human hepcidins 115 , gads 116 clavanins and styelins 117 from marine organisms, and a range of synthetic peptides [118][119][120][121] , along with the anticancer activity of a variety of AMPs 16 . For the most, part, these studies have focussed on cationic AMPs and there has been less research into the effects of pH on anionic AMPs 94,95 .…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the addition of a His6-tag increases the binding strength of LF N by approximately threefold at pH c|t 5.5|5.5 75 and restores the binding activity to neutral and negatively charged mutants of LF N 27. 125 His residues are also responsible for pH-dependent rearrangement of proteins, such as the pHdependent coil-helix transition of glycinamide ribonucleotide transformylase, 126 acidic activation of His-rich synthetic peptides aimed at disrupting microbial membranes, 127 and enhancing gene transfer though membrane permeabilization of human tumor cells. There are several potential interactions that may contribute to the destabilization of the membrane spanning region of the PA 63 pore and the membrane.…”
Section: Hypothetical Mechanismmentioning
confidence: 99%
“…The pH ranges at which these transitions occur suggest that the protonation of His side chains may be involved. Indeed, it has been shown that His residues may function as pH sensors for many molecular mechanisms involving protein-membrane interaction (11,12) and/or MG formation (13,14).…”
mentioning
confidence: 99%